Characterization of Non-selected Intermolecular Gene Conversion in the Polyploid Haloarchaeon Haloferax volcanii - Wasser, Daniel; Borst, Andreas; Hammelmann, Mathias; Ludt, Katharina; Soppa, Jörg (Frontiers in Microbiology, 2021)
Gene conversion is defined as the non-reciprocal transfer of genetic information from one site to a homologous, but not identical site of the genome. In prokaryotes, gene conversion can increase the variance of sequences, like in antigenic variation, but can also lead to a homogenization of sequences, like in the concerted evolution of multigene families. In contrast to these intramolecular mechanisms, the intermolecular gene conversion in polyploid prokaryotes, which leads to the equalization of the multiple genome copies, has hardly been studied. We have previously shown the intermolecular gene conversion in halophilic and methanogenic archaea is so efficient that it can be studied without selecting for conversion events. Here, we have established an approach to characterize unselected intermolecular gene conversion in Haloferax volcanii making use of two genes that encode enzymes involved in carotenoid biosynthesis. Heterozygous strains were generated by protoplast fusion, and gene conversion was quantified by phenotype analysis or/and PCR. It was verified that unselected gene conversion is extremely efficient and it was shown that gene conversion tracts are much longer than in antigenic variation or concerted evolution in bacteria. Two sites were nearly always co-converted when they were 600 bp apart, and more than 30% co-conversion even occurred when two sites were 5 kbp apart. The gene conversion frequency was independent from the extent of genome differences, and even a one nucleotide difference triggered conversion.